Immigration Policy in the Crossfire of Neoliberalism and Neonationalism - Joppke Christian (Swiss Journal of Sociology, 2021)
Previous scholarship has looked at Western states’ immigration policies from the vantage point of advancing liberalism. This perspective needs to be updated by including two additional factors: neoliberalism and a new nationalism that arises in its context, typically in the form of populist right parties. I argue that contemporary immigration policy is bifurcated into two policies with opposite logics: one of proactively courting the top, and another of reactively fending off the bottom. This dual structure is best explained in neoliberal terms, with neonationalism merely reinforcing but not generating it.